Development of an integrated avionics hardware system for unmanned aerial vehicle research purposes - Van Wyk, Robin (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2011.